Euthanasia: an Active Area Of Research In Contemporary Bioethics: Challenges For The Society And The Professionals Of Health-Care - Tsounis, Andreas; Malliarou, Maria; Sarafis, Pavlos (My University, 2012)
Introduction: Euthanasia refers to the practice of intentionally ending a life in order to relieve pain and suffering. Aim of this review is to present different views and arguments about euthanasia and to discuss the legal regulations and the way that modern societies confront the inevitable dilemmas that it brings in surface. A literature review was conducted on google scholar for articles about the theme using as key words: euthanasia, active, passive, pros/cons, legislation. Results: The results of the literature review came up with its pros and cons of it. Some of the pros are that it provides a way to relieve extreme pain, a way of relief when a person's quality of life is low and an insurance of the rights of dignity and self-determination. The basic cons of it is that it devalues human life, it has become a means of health care cost containment and that there are objections about the expressions of willingness for people under high psychological pressure or for population groups like older people with dementia or mentally ill. Under the pressure of the new circumstances in the last decades, Euthanasia became the subject of legislative interventions in a number of countries. But even the most complete regulatory framework cannot predict all the aspects. Every different case will always be a confrontation with important existential and emotional issues. Conclusion: Before resulting in Euthanasia, a person must consider the situation. There are a lot of circumstances under which euthanasia is a reasonable and responsible choice. Each case is different from another.
Keywords: Euthanasia; Legal regulations; Literature review